MRI-GUIDED DISSECTION OF THE NONHUMAN PRIMATE BRAIN: A CASE STUDY - Daunais, James Bernard (2009)
Numerous biochemical as well as electrophysiological techniques require tissue that must be retrieved very quickly following death in order to preserve the physiological integrity of the neuronal environment. Therefore, the ability to accurately predict the precise locations of brain regions of interest (ROI) and to retrieve those areas as quickly as possible following the brain harvest is critical for subsequent analyses. One way to achieve this objective is the utilization of high resolution MRI scans to guide the subsequent dissections. In the present study, individual MRI scans of the brains of rhesus and cynomolgus macaques that had chronically self-administered ethanol were employed in order to determine which blocks of dissected tissue contained specific ROIs. MRI-guided brain dissection of discrete brain regions was completely accurate in 100% of the cases. In comparison, approximately 60–70% accuracy was achieved in dissections that relied on external landmarks alone without the aid of MRI. These results clearly demonstrate that the accuracy of targeting specific brain areas can be improved with high-resolution MR imaging.